THE ROLE OF THE ROKAT TASE’ CEREMONY IN THE DEVELOPMENT OF RELIGIOUS VALUES AND SOCIAL VALUES IN BRANTA VILLAGE, TLANAKAN DISTRICT, PAMEKASAN REGENCY: PERAN UPACARA ROKAT TASE’ DALAM PENGEMBANGAN NILAI RELIGIUS DAN NILAI SOSIAL DI DESA BRANTA KECAMATAN TLANAKAN KABUPATEN PAMEKASAN - Khomsiyatil Askinah; Dwi Retnani Srinarwati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Rokat Tase' is a tradition carried out by the Madurese people which is also called basic rokat. In general, Rokat Tase' is practiced by fishermen and is associated with religious values ​​and religious rituals with the intention of being a form of gratitude to God Almighty for the blessings of safety and good fortune received. This research aims to determine the process of implementing the Rokat Tase' ritual, the values ​​developed in the Rokat Tase' ritual process in the development of religious values ​​and social values. This research is a type of qualitative research conducted in Branta Village, Tlanakan District, Pamekasan Regency. Data sources were obtained from local community leaders, then supported by village documents and archives. Data collection was carried out using interview, observation and documentation techniques. The results of the research show that Rokat Tase' takes place once a year and the performance is adjusted to the tides. The series of events for the Rokat Tase' Ceremony include chanting and praying together, making and decorating miniature boats, sailing on the sea and entertainment events. The values ​​developed during the implementation process are social values, religious values ​​and traditional values. Rokat Tase' plays a role in developing religious and social values ​​by optimizing the field of education in coordination with nature and routinely implemented in community traditions.